IMPLEMENTASI KEBIJAKAN PENANGGULANGAN BENCANA DI KABUPATEN PARIGI MOUTONG - Dirwan, Fadlin (Katalogis, 2017)
This research aims to know the implementation of disaster mitigation Policies in Parigi Moutong Regency, usefulness in the study as reference material to the development of science in the science of public administration in particular, in this research uses qualitative research methods. To perform the data collection techniques by conducting in-depth interviews, observation and documentation. Researchers conduct interviews with 5 (five) the informant was selected by asking questions related to the 6 (six) the variable policy implementation model of Van Meter and Van Horn in Agustino. As for the stages in a State of disaster: before the disaster, while disaster and after the disaster. The research results indicate (1) the implementation of disaster mitigation Policies in the Regency Parigi Moutong that targets, standards and policies that existed for this has not been effective so that the need for improvements in accordance with the policy objectives. Human resources is in compliance with the mechanism just yet effective, whereas the implementing agent characteristics sometimes policy has not been in accordance with the needs of the community since it has yet to match the standard work procedures or Standard Operating Procedures (SOP), communication between the associated organisations is still less so that the submission of information to the implementing policy on what the standards and goals are not uniform and consistent so that the occurrence of mis of communications at the time of the disaster with disaster relief coordinator between relevant parties.